From Liquid to Solid-State Fluorescence: Tricyclic Lactones Based on 4-Hydroxy-1,3-thiazoles - Calderón Ortiz, Lorena K.; Würfel, Hendryk; Täuscher, Eric; Weiß, Dieter; Birckner, Eckhard; Görls, Helmar; Beckert, Rainer (Synthesis, 2014)
This work describes the synthesis of a series of tricyclic lactones based on 4-hydroxy-1,3-thiazoles prepared by the classic Hantzsch synthesis. The tricyclic lactones are more rigid than the parent 4-hydroxythiazoles and are featured not only by fluorescence in solution, but also in the solid state. An extension of the chromophoric system was successfully realized by integration of the benzothiazole substructure, thus resulting in bathochromic shifts of absorption and also fluorescence. The new synthesized lactones additionally show interesting properties in solution, whereby the initial blue fluorescence changes dramatically with a variation of the pH value.
Keywords: heterocycles; chromophores; fused-ring systems; thiazole; fluorescence